FRI0234 BehÇet's disease: Clinical and immunologic manifestations in a cohort of 377 patients. (23rd January 2014) - Rodríguez Carballeira, M.; Solans, R.; Martínez, F.; Larrañaga, J.; Rios, R.; Ortego, N.; Callejas, J.L.; Castillo, M.J.; Martínez-Berriotxoa, A.; Trapiella, L.; Solanich, X.; Muñoz-Rodríguez, F.; et al.
Abstract : Objectives: To analyze the demographic and clinical manifestations of Behçet's disease (BD) in a large cohort of patients. Methods: The demographic and clinical features of BD in 377 patients who met the proposed criteria for the classification of BD (ISBD) from 10 Spanish centres were analyzed. This project was performed under the auspices of the Working Area of BD, on behalf of Systemic Autoimmune Diseases Group (GEAS) of Spanish Society of Internal Medicine (SEMI). This registry started in 2009, with a multicenter, consecutive, retrospective design. Results: The cohort consisted of 196 female patients (52%) with a mean ± SD age of 28.6±12.1 years. The median delay in diagnosis was 24 months (range 0-420). There were 349 Caucasian patients (92.6%), 19 Arabic (5%), and 9 patients of other races (2.4%). The median follow-up was 140.5 months (range 0-439). The most common presenting manifestations were ulcers (74%; oral ulcers 35.3%, genital ulcers 2.1%, both 37%), fever (6%), anterior uveitis (5.1%), arthritis 3.5%, retinal vasculitis (1.9%), erythema nodosum (1.9%), posterior uveitis (1.3%), aseptic meningitis (1.1%), pseudofolliculitis (0.5%) and other manifestations less frequent. A great variety of clinical manifestations were recorded during the evolution in almost all organ systems: oral ulcers (100%), genital ulcers (74%), arthritis (39.2%), pseudofolliculitis (48.8%), erythema nodosum (37.9%), ocular involvement (35.3%) in form of anterior uveitis (26.7%), retinal vasculitis (12%), posterior uveitis (8.8%), venous thrombosis (18%; 4 cases in cerebral venous sinus, 2 retinal venous thrombosis, 3 inferior vena cava thrombosis, one patient with Budd-Chiari syndrome, and the remaining were deep venous thromboses), fever (16%), vasculitis (9%), aseptic meningitis (6.9%), pseudotumor cerebri (2.9%), stroke (2.9%), arterial aneurysms (1.1%), and other disorders of central nervous system in 11%. Considering visual involvement, 16.8% of patients presented with visual acuity deficit which represents 47.7% of all patients with ocular involvement. The most frequently used treatment was oral corticosteroids (79.3%) followed by colchicine (76.5%). Interestingly, 54.5% of patients required any immunosuppressive treatment during the follow-up. Oral anticoagulation was used in 16.7% of patients. Finally, anti-TNF therapies were used in 10.9% of patients and only 4.5% received thalidomide. In order of frequency, the main adverse effects of treatment were hypertension (6.9%), infections (6.4%), cataract (5.7%), osteopenia (2.9%), renal failure (2.1%), diabetes mellitus (1.9%), aseptic necrosis of femoral head (1.1%), and bone marrow toxicity (1.3%). Three patients have died since the beginning of the registry. Conclusions: The main clinical features of BD patients of our Registry are similar to those of other series with the same ethnic origin. Disclosure of Interest: None Declared